The Impact of Trade Promotion on Sales Volume in the Beer Industry - Ndem; Etim, Samuel; Ezekiel; Sunday, Maurice (British Journal of Marketing Studies, 2019)
This study was on trade promotion and its impact on sales growth of the Guinness Plc Nigeria. The Nigeria beer industry is the second largest in Africa. The extensive use of trade promotions in industry does not have any corresponding research to show the potency of most of the tools used on sales volume. This gap represents the research interest that was predicted on three major objectives of trade promotion tool; buying allowance, sales contest and special allowance used in the industry. A survey research design was applied in the course of the study, with a well-designed questionnaire on the subject matter. A simple random sampling technique was used for sample selection. The analysis of 36 questionnaires from wholesaler and retailer of Guinness product, with a simple regression model on statistical package for social science (SPSS) indicated that sales contest, special allowance, and buying allowance impact on sales volume of Guinness products but with varying strength of prediction. It was concluded that the varying strength of the sales tools, should be given attention according to their predictive ability on sales volumes. Justice and equity should be at best practice in implementing trade promotion.